2021
DOI: 10.1021/acsami.1c04226
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Imaging of Nanoscale Contact with Förster Resonance Energy Transfer

Abstract: Adhesion is caused by molecular interactions that only take place if the surfaces are in nanoscale contact (NSC); i.e., the distance between the surfaces is in the range of 0.1–0.4 nm. However, there are several difficulties measuring the NSC between surfaces, mainly because regions that appear to be in full contact at low magnification may show no NSC when observed at higher magnifications. Thus, the measurement area of NSC is very small with imaging techniques, and an experimental technique to evaluate NSC f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…4−8 Therefore, the adhesion between two surfaces is proportional to its NSC area, and can only be properly investigated if the associated degree of NSC is correctly evaluated. 9 However, we still cannot gain insight into it due to the physical difficulties of looking directly at the NSC. Here, we tailored a FRET-based experimental technique to enable access to NSC and provide a quantification approach.…”
Section: Measurement Of Nsc Between Surfaces Using Fretmentioning
confidence: 99%
See 3 more Smart Citations
“…4−8 Therefore, the adhesion between two surfaces is proportional to its NSC area, and can only be properly investigated if the associated degree of NSC is correctly evaluated. 9 However, we still cannot gain insight into it due to the physical difficulties of looking directly at the NSC. Here, we tailored a FRET-based experimental technique to enable access to NSC and provide a quantification approach.…”
Section: Measurement Of Nsc Between Surfaces Using Fretmentioning
confidence: 99%
“…Recently it has been demonstrated that the NSC measured with FRET correlates to the adhesion between soft materials. These studies showed that for bonded thin films pressed under different loads, the FRETeff and adhesion increase with the applied pressure, caused by the correspondent increase of the degree of NSC . Thus, FRET has been introduced as a proper technique to quantify the degree of NSC and establish a relation between FRETeff and adhesion in bonded films.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, we built a simple but highly ordered system, with Förster resonance energy transfer (FRET). Simões et al recently showed the application of a similar idea, with the assembly of two thin films composed of simple organic fluorophores for the quantification of nanoscale contacts [22]. FRET networks have been proposed for broadening the possible utilization of FRET-based biosensors [23].…”
Section: Introductionmentioning
confidence: 99%